Influence of Beam-to-Column Connections in the Seismic Performance of Precast Concrete Industrial Facilities. Issue 4 (2nd October 2022) - Rodrigues, Hugo; Vitorino, Hugo; Batalha, Nádia; Sousa, Romain; Fernandes, Paulo; Varum, Humberto
Abstract: Past earthquakes have brought attention to the poor performance of precast reinforced concrete structures, especially relating to beam-to-column connections. The evaluation of different methodologies for the analysis of beam-to-column connections in industrial buildings is important. In the present work numerical analyses developed allowed the study of the effect that different story heights and connection properties have on frequencies, drifts, seismic coefficients and connection sliding. The results showed that the friction between concrete elements and the consideration of neoprene have a small impact on the drift demands in the columns and the seismic coefficients of the structures analyzed; on the other hand, the effect of steel dowel on the drift demands and seismic coefficients is significant. The comparison of models with different properties and connections allowed a better understanding of the parameters that affect the seismic behavior of precast reinforced concrete buildings the most and provide indications for building more accurate and efficient numerical models.